KESADARAN HUKUM MAHASISWA TERHADAPiUNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DANiANGKUTANiJALAN (STUDI KASUS KEPEMILIKANiSURAT IZINi MENGEMUDI MAHASISWA ANGKATAN 24) - Oktavianti, Bulan; Hendra, Hendra; Wela Sasih , Agustin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study analyzes the legal awareness of PPKn students of the 2024 cohort at Universitas Jambi regarding the obligation to obtain a Driving License (SIM) under Law No. 22 of 2009 on Traffic and Road Transportation. Despite knowing the legal obligation, many students still drive without a SIM, reflecting a gap between legal knowledge and actual compliance. Using a qualitative case study approach, data were collected through in-depth interviews with seven students without SIM and one law lecturer, supplemented by documentation. Data analysis followed Miles and Huberman’s model: data reduction, display, and conclusion drawing. Findings indicate that students’ legal awareness is at a moderate level. While their cognitive understanding of the law is adequate, it has not translated into behavioral compliance. The main inhibiting factors are non-financial, including perceptions of complicated administrative procedures, academic busyness leading to procrastination, peer influence that normalizes non-compliance, and the lack of police raids around the campus. The study concludes that legal awareness among PPKn students requires improvement through contextual education, simplified SIM access, and strengthening internal motivation to align legal knowledge with consistent real-world action. As future educators, these students must internalize traffic law compliance as a moral responsibility and social exemplar.